Stent dislodgement in left anterior descending coronary artery and successful deployment with two parallel wires and a small balloon - Ngow, Harris Abdullah (Polish Cardiac Society, 2009)
Coronary artery stent dislodgement during angioplasty is a rare complication. Stent dislodgement was more frequent in the past when stents were manually crimped onto the balloon. Newer and improved balloon-mounted stents with better radio-opacity have reduced the incidence of stent dislodgement but do not completely eliminate it. We report a case of balloon-mounted stent dislodgement in the proximal left anterior descending (LAD) coronary artery prior to deployment. This patient however was successfully treated with re-wiring of the artery with two parallel wires and the stent’s reposition prior to deployment with the help of a small balloon.